AGEING IN INDIA - A CONCEPTUAL CLARIFICATION IN THE BACKGROUND OF GLOBALIZATION - Nair, Lekshmi V (European Scientific Journal, ESJ, 2014)
The multifarious dimensions of ageing in India can sociologically be thought to be a series of transition from one set of social roles to another and such roles are structured by the social system. It may be mentioned that the process of ageing is not uniform for all individuals in the society. Thus, changes in the life of the old age, which is considered to be the sanyas ashram of the Hindu ashram theory, is influenced by the biological as well as the social and cultural systems. However, in recent times, the status and role of the old age population have been changed due to the technological developments that have colonized the outlook of the youths. The present paper tries to analyse how the recent development of globalization have changed the concept of ageing in India